Opinion of Young People on the Crises of Emerging Adulthood: Premarital Sex, Ex-nuptial Pregnancy and Infant Abandonment - Razali , Salmi; Daud, Suzanna; Abdullah, Bahiyah; Ariffin , Farnaza (Environment-Behaviour Proceedings Journal, 2021)
Premarital sex, ex-nuptial pregnancy and infant abandonment are increasing problems. This study aimed to explore the opinion of youngsters on the contributing factors of this triad. A focus group discussion was conducted among 59 consented youngsters who were clustered into six groups. Standard prompts were given, discussions were audiotaped, transcribed and thematically analysed. Main themes emerged as the contributing factors include adjustment with the transition in life, conflict in relationships and lacking internal defences. Understanding these factors within the social development of youngsters is essential to equip them in making an informed decision on their sexuality and crises in life. Keywords: ex-nuptial pregnancy, infant abandonment, premarital sex, youngsters eISSN: 2398-4287Â© 2021. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians/Africans/Arabians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI:https://doi.org/10.21834/ebpj.v6iSI4.2896